2018
DOI: 10.1042/cs20180403
|View full text |Cite
|
Sign up to set email alerts
|

The down-regulation of hsa_circ_0012919, the sponge for miR-125a-3p, contributes to DNA methylation of CD11a and CD70 in CD4+ T cells of systemic lupus erythematous

Abstract: Background: Systemic lupus erythematous (SLE) is an autoimmune disease characterized by the production of autoantibodies directed against various autoantigens. But the expression profiles and functions of circular RNAs (circRNAs) in SLE are still scarce. Objectives: To explore the roles of circRNA in SLE and its potential diagnostic potential in SLE. Methods: SLE patients and healthy control subjects were recruited. CD4+ T cells were isolated, circRNA microarray analysis were used to screen for circRNA candida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 25 publications
2
70
0
Order By: Relevance
“…It was reported that RANTES is involved in the development of SLE, and the transcriptional factor KLF13 regulates the expression of RANTES in activated T cells (100). Zhang et al (101) demonstrated that hsa_circ_0012919 is highly expressed in lupus CD4 + T cells and participates in regulating the expression of RANTES and KLF13 by serving as the miR-125a-3p sponge. Moreover, inhibiting hsa_circ_0012919 corrects the DNA hypomethylation of CD70 and CD11a in lupus CD4 + T cells by promoting DNMT1 activity (101).…”
Section: The Roles Of Ncrnas In the Aberrant Activation And Differentmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that RANTES is involved in the development of SLE, and the transcriptional factor KLF13 regulates the expression of RANTES in activated T cells (100). Zhang et al (101) demonstrated that hsa_circ_0012919 is highly expressed in lupus CD4 + T cells and participates in regulating the expression of RANTES and KLF13 by serving as the miR-125a-3p sponge. Moreover, inhibiting hsa_circ_0012919 corrects the DNA hypomethylation of CD70 and CD11a in lupus CD4 + T cells by promoting DNMT1 activity (101).…”
Section: The Roles Of Ncrnas In the Aberrant Activation And Differentmentioning
confidence: 99%
“…Zhang et al (101) demonstrated that hsa_circ_0012919 is highly expressed in lupus CD4 + T cells and participates in regulating the expression of RANTES and KLF13 by serving as the miR-125a-3p sponge. Moreover, inhibiting hsa_circ_0012919 corrects the DNA hypomethylation of CD70 and CD11a in lupus CD4 + T cells by promoting DNMT1 activity (101). The AKT signaling is over-activated in CD4 + T cells from SLE patients (102)(103)(104).…”
Section: The Roles Of Ncrnas In the Aberrant Activation And Differentmentioning
confidence: 99%
“…CircRNAs have been identified as a determinant factor in many human diseases, including cardiovascular system diseases, neurological disorders, and cancer. Moreover, several studies have demonstrated that circRNAs can serve as prognostic biomarkers because of their characteristics [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang C et al isolated CD4 + T cells where circRNA microarray study was conducted for screening out circRNA candidates. As indicated from the results, circ_0012919 reduction enriched the expression of DNMT1, decreased the expressions of CD70 and CD11a, and reversed the DNA hypomethylation of CD11a and CD70 in CD4 + T cells of systemic lupus erythematosus (SLE); however, it was reversible by DNMT1 reduction [51]. Circ_0005519 was reported to be upregulated and negatively related to hsa-let-7a-5p expression in CD4 + T cells of asthmatic cases.…”
Section: Circular Rnas In Immune Responses and Diseasesmentioning
confidence: 86%